I vissuti delle vittime in emergenza: la formazione tra spiegazione e comprensione - Fabio Sbattella (Rivista di Psicologia dell'Emergenza e dell'Assistenza Umanitaria, 2012)
This article aims at highlighting the risks of an undifferentiated training in emergency psychology. It also discusses the different training and information needs of volunteers and emergency workers. We propose to carefully reflect on the learning objectives in relation to the specific roles and tasks of the different categories of people involved in emergency. In terms of contents, we propose to distinguish between the “understanding” needs and “explanation” needs in relation to the behaviour of the victims in an emergency. Cultivating “understanding” skills rather than "explanation" skills can encourage the development of appropriate attitudes in rescuers and volunteers who don’t have a deep knowledge of psychology.